Malaria incidence during early childhood in rural Burkina Faso: analysis of a birth cohort protected with insecticide-treated mosquito nets - Wehner, Sabrina; Stieglbauer, Gabriele; Müller, Olaf (Acta tropica, 2017)
Background - Even in the high transmission areas of sub-Saharan Africa (SSA), the incidence of falciparum malaria varies greatly depending on factors such as age, rainfall pattern, distance to breeding places, quality of houses, and existing vector control measures. Insecticide-treated mosquito nets (ITN) have now become the vector control standard in nearly all of SSA. This study aims to describe and analyse the incidence of malaria in a cohort of young children protected with ITN in rural West Africa. - Methods - Data of a subsample from a large community trial in rural north-western Burkina Faso consisting of 420 children were analysed. The main aim of the trial was to evaluate the long-term effects of ITNs in two groups of new-borns; Group A was protected with ITN from birth onwards while Group B was protected only from month six onwards. The primary objective of this study was to describe malaria incidence in detail with an analysis of the impact of potentially relevant determinants of malaria incidence, in particular age, sex, ITN protection, village, month and season as secondary objective. Bivariate negative binomial regression analysis was used to calculate incidence rate ratios of malaria incidence. Moreover, relevant variables were included in a multivariate negative binomial regression model to examine possible risk factors for malaria. - Results - Out of the 420 study children 387 (92.1%) developed a total of 1822 falciparum malaria episodes; the malaria incidence rate was 7.6 per 1000 child days. Group A children had lower malaria incidence rates compared to group B, but only in early infancy. Malaria incidence varied significantly between villages and increased with age, but no sex-specific differences were observed; these findings were confirmed in the multi-variate analysis. Malaria incidence peaked sharply towards the end of the rainy season in September but there were no differences in the seasonal pattern by study group. - Conclusions - The study, carried out in a high-transmission West African area, shows that malaria incidence remains high in spite of maximum ITN coverage.
Gesehen am 29.05.2019